Cell signalling pathways and RNAi - O'Grady, Michael (Henry Stewart Talks, 2007)
Use of functional cell-based reporter system (Cell Sensor(tm) technology) with RNAi, From target knockdown to compound screening and verification in biochemical assays, Analysis of small-molecule protein kinase inhibitors, Epidermal growth factor receptor (EGFR) signalling pathway, StealthTM RNAi, second-generation RNAi compounds, Integration of a cell-based assay system, RNAi and biochemical assay technologies, Kinase discovery platform to identify biologically relevant kinase targets, Characterization of kinase inhibitors in systems, Possible synergistic effects of combining RNAi and kinase inhibitors
Reviewed at 2015/11/13